A New Nanotechnology for Imaging the Juxta‐Articular Intraosseous Vasculature‐Canal Complex and Related Clinical Pilot Studies - Mengmeng Dou; Jinfeng Yang; Jiaoran Li; Jianmin Li; Zhenzhong Li; Xianhao Shao; Xia Su; Jing Li; Guanghui Wang; Kun Cheng (Orthopaedic Surgery, 2025)
ABSTRACT Objective The objective of this study is to achieve distinct visualization of juxta‐articular intraosseous microvessels, a novel nanoimaging methodology in which superparamagnetic iron oxide nanoparticles and meglumine diatrizoate (MD) are used cooperatively was implemented. Methods A newly created composite of MD and Fe3O4 nanoparticles (MD‐Fe3O4 NPs) was prepared as a contrast agent to achieve efficacious imaging of the juxta‐articular intraosseous vasculature‐canal complex (JIVCC). Scanning electron microscopy (SEM) and energy dispersive spectrum (EDS) were employed to observe the structural characteristics and binding stability of the MD‐Fe3O4 NPs. In 20 rabbits that received an injection of MD‐Fe3O4 NPs, 1‐mm‐thick computed tomography (CT) scanning was performed for radiographic assessment. Hematoxylin–eosin‐ and potassium ferrocyanide‐stained sections from 10 sacrificed rabbits were used to observe the histological characteristics of JIVCC with MD‐Fe3O4 NPs, and the remaining 10 rabbits were utilized for a systemic safety evaluation. After a healthy volunteer received an MD‐Fe3O4 NP injection, we also performed CT scanning and related safety evaluations. Results When the MD nanoparticles and amino‐Fe3O4 nanoparticles were mixed together, they aggregated into a stable compound structure according to microscopic observations and SEM–EDS verification. In 20 rabbits receiving MD‐Fe3O4 injections, 1‐mm slice CT imaging demonstrated significantly enhanced visualization of the JIVCCs in magnet‐placed knees compared to contralateral limbs (tibial JIVCC: p < 0.001; femoral JIVCC: p < 0.001), confirming MD‐Fe3O4 NPs as the efficacious magnetic contrast enhancer. The histological characteristics of MD‐Fe3O4 NPs in JIVCC were revealed. The levels of serum iron before and 4 and 72 h after MD‐Fe3O4 NP injection were 23.9 ± 2.13 μmol/L, 26.2 ± 2.30 μmol/L, and 24.9 ± 2.33 μmol/L, respectively, indicating that there was no significant difference in safety (p = 0.092). After a volunteer received MD‐Fe3O4 NPs via intravenous administration, the JIVCC was clearly visualized, laboratory tests of serum iron levels were normal, and no injection‐related complications occurred. Conclusions A novel compound nanoparticle, which achieved satisfactory overall outcomes, was implemented as an appropriate alternative for the discernible visualization of juxta‐articular intraosseous microvessels. The nanotechnology utilized in this study may augment the clinical imaging methodology for the osseous vascular system.